If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2-x+14=2x(x-3)
We move all terms to the left:
x2-x+14-(2x(x-3))=0
We add all the numbers together, and all the variables
x^2-1x-(2x(x-3))+14=0
We calculate terms in parentheses: -(2x(x-3)), so:We get rid of parentheses
2x(x-3)
We multiply parentheses
2x^2-6x
Back to the equation:
-(2x^2-6x)
x^2-2x^2-1x+6x+14=0
We add all the numbers together, and all the variables
-1x^2+5x+14=0
a = -1; b = 5; c = +14;
Δ = b2-4ac
Δ = 52-4·(-1)·14
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{81}=9$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-9}{2*-1}=\frac{-14}{-2} =+7 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+9}{2*-1}=\frac{4}{-2} =-2 $
| 40+22.50x=940 | | 4x+-10=46+13x | | 3(7x-7)-6=99 | | (x+20)+x+30=180 | | 4p+12=-8 | | s2=334 | | 6q+6=3q | | 8x+7=9x-9 | | T(x)=75x+759 | | -5(x+1)+3x=6-(4x-5) | | -8-b=12 | | 5-22/3x=1/3 | | -8r-36=-6(1+8r) | | 200m-75m+62075=66625-200m | | -15+8a=20+3a | | 3x-1-4x+21=33 | | 3.2-10=2.4x+6 | | x+53+65+70=180 | | -4(x-11)=-20 | | 8-k=13 | | 11+3/4x=-13 | | 11+3/4x=-12 | | 1/4x+5=20 | | 1/3a+-12=4/3a+6 | | -5(2x-4)+6=6x+5+3x+8 | | 11−m=51−6m | | 5.4+x=7.5 | | 22=1+8a+5 | | X+x/3=2 | | 12-3g=18 | | -33+4x=3 | | 3v+24=6v |